Thermal diffusivity of in-situ exfoliated graphite intercalated compound/polyamide and graphite/polyamide composites - S. R. Kim; M. Poostforush; J. H. Kim; S. G. Lee (eXPRESS Polymer Letters)
The thermal diffusivity of graphite intercalated compound (GIC)/polyamides (PA6, PA66 and PA12) and graphite/polyamides composites were investigated. The polyamides/GIC composites were prepared by an in-situ exfoliation melting process and thermal diffusivity of the composites was measured by a laser flash method. The surface chemistry of the GIC and graphite was investigated using Fourier transform infrared spectroscopy, the fracture morphology of the composites was observed by field emission scanning electron microscopy. The thermal diffusivity of the in-situ exfoliation processed PA/GIC composites showed a significant improvement over those of PA/expanded graphite intercalated compound composites and PA/graphite composites. We suggest that the larger flake size and high expansion ratio of the GIC during the in-situ exfoliation process leads to 3-dimensional conductive pathways and high thermal diffusivity. Thermal diffusivity of the polyamides/GIC (20 vol%) composites was increased approximately 18 times compared to that of pure polyamides.